Poverty and fertility in less developed countries: a comparative analysis - Arnstein Aassve; Henriette Engelhardt; Francesca Francavilla; Abbi Kedir; Jungho Kim; Fabrizia Mealli; Letizia Mencarini; Stephen Pudney; Alexia Prskawetz (University of Essex, Institute for Social and Economic Research (ISER), 2005)
Just as poverty analysis has a central part in Development Economics, studies of fertility behaviour have an equally important standing in the Demography literature. Poverty and fertility are two important aspects of welfare that are closely related. In this paper we use unique longitudinal data sources to study the relationship between poverty and fertility at household level over a two to five year period. In particular we compare the relationship between fertility and poverty in four countries: Albania, Ethiopia, Indonesia and Vietnam. These countries differ greatly in their history, average income, social structure, economic institutions and demographic features. We find that there is a substantial difference in the relative importance of the determinants of poverty dynamics and fertility; the persistence of high levels of fertility and poverty in Ethiopia is driven by lack of economic growth and poor access to family planning; education and health provision are crucial elements in reducing poverty and fertility, as is clear from Vietnam, Indonesia and Albania.
Keywords: 330